125k views
0 votes
Distribute and then combine like terms. 2(3a-6b)+c-4a+b

1 Answer

5 votes

Answer:

2a-11b+c

Step-by-step explanation:

Given the expression:


2\left(3a-6b\right)+c-4a+b

First, we distribute:


\begin{gathered} =2\left(3a)-2(6b\right)+c-4a+b \\ =6a-12b+c-4a+b \end{gathered}

Next, we bring the like terms together in order to combine them:


=6a-4a-12b+b+c

Make sure the number of terms is the same when you rearrange ( in this case 5).

Then we combine to obtain:


=2a-11b+c

User Greim
by
8.0k points